Preparation and characterization of glass-ceramic synthesized from soda lime glass and wastewater sludge - Abdul Wahab, Zaidan; Zaibon, Syaharudin; Matori, Khamirul Amin; Edros, Norfarezah Hanim; Thai, Ming Yeow; Mayzan, Mohd Zul Hilmi; Mohd Ghazali, Mohd Sabri; Md Daud, Mohd Norizam (Universiti Putra Malaysia Press, 2010)
This paper reports an alternative method for making glass-ceramic from disposal waste water sludge and soda lime silica (SLS) glass. The glass ceramic samples were prepared from a mixture of wastewater sludge and SLS glasses, melted at 1375°C for 3 hours and quenched by pouring into water to obtain a coarse frit. The frit glass was then crushed and sieved to 106μm before it was pressed to a pellet. The sintering process was performed at various temperatures between 700- 1000°C for 2 hours and morphologically characterized with XRD, SEM, and EDX. Overall results showed the crystalline phase of diopside sodian-critobalite glass-ceramic is depending on thermal treatment process and making them attractive to industrial uses such as in construction, tiling, and glass-ceramic applications.